Research in protected areas: fire in Parque Nacional Lihué Calel, La Pampa, Argentina (Semiárida, 2024)
Protected Areas (PAs) play a crucial role in the conservation and appreciation of the biological, ecological and socio-cultural elements of the landscape. These areas, in line with their creation objectives, provide various environmental services such as watershed protection, landscape and biodiversity preservation, and regulation of ecosystem processes. Additionally, they offer opportunities for research, education, and environmental training. Researchers from the Facultad de Agronomía, UNLPam are currently conducting two projects related to the theme of fire in Parque Nacional Lihué Calel, focusing on the impact of recurrent wildfires and the assessment of prescribed burns. Undertaking such investigations within a national park creates an interdisciplinary and interinstitutional working space, addressing various topics with the aim of transforming gathered information into practical management tools. Collaboration with PA technicians is essential to achieve the proposed objectives and serves as the link between information generation and effective implementation.
Keywords: interdisciplinary and interinstitutional work; wildfires; prescribed burning; shrublands; National Parks Administration (APN)